KARAKTERISTIK YESUS DALAM MATIUS 9:9-13 SEBAGAI FONDASI KEPRIBADIAN GURU PENDIDIKAN KRISTEN - Lumintang, Marcellius; Margareta Clara, Grace; Umboh, Satria Evans (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2024)
One of the mandatory competencies for teachers in Indonesia is personality. Personality competence is a crucial aspect in shaping the character of students, and the personality competence of Christian education teachers is acquired through learning and experience. For Christian education teachers, it can also be derived from the example of Jesus Christ, the Great Teacher, based on biblical principles. This study aims to explore the characteristics of Jesus in Matthew 9:9-13 and how these characteristics serve as a foundation for the personality of effective Christian education teachers. This research employs a qualitative descriptive approach using text analysis and literature review methods. The results of this study indicate that the competence and professionalism of Christian education teachers need to be supported by the following attitudes: Leadership characterized by sensitivity and initiative in recognizing opportunities and converting them into actions; Open-mindedness, meaning refraining from making justifications or building subjective assumptions about students; Advocacy, which involves defending, accompanying, and providing answers concerning hope. This study recommends a personality competence model for Christian education teachers based on Leadership Characteristics, Open-mindedness, and Advocacy as a foundation and indicator for assessing the personality of Christian education teachers.